Mutant neoliberalism : market rule and political rupture - Callison, William; Manfredi, Zachary (Fordham University Press, 2020)
This interdisciplinary collection, featuring some of today's most prominent political theorists, sociologists, philosophers, and historians, challenges narratives of neoliberalism's demise. The book queries whether contemporary political ruptures--including the rise of far-right forces--will challenge, support, or extend the reach of market rule around the globe.